Safety and Pharmacokinetics of Double-Dose Lopinavir/Ritonavir + Rifampin Versus Lopinavir/Ritonavir + Daily Rifabutin for Treatment of Human Immunodeficiency Virus–Tuberculosis Coinfection. (9th February 2021) - Kendall, Michelle A; Lalloo, Umesh; Fletcher, Courtney V; Wu, Xingye; Podany, Anthony T; Cardoso, Sandra W; Ive, Prudence; Benson, Constance A
Abstract: Background: Protease inhibitor-based antiretroviral therapy may be used in resource-limited settings in persons with human immunodeficiency virus and tuberculosis (HIV-TB). Data on safety, pharmacokinetics/pharmacodynamics (PK/PD), and HIV-TB outcomes for lopinavir/ritonavir (LPV/r) used with rifampin (RIF) or rifabutin (RBT) are limited. Methods: We randomized adults with HIV-TB from July 2013 to February 2016 to arm A, LPV/r 400 mg/100 mg twice daily + RBT 150 mg/day; arm B, LPV/r 800 mg/200 mg twice daily + RIF 600 mg/day; or arm C, LPV/r 400 mg/100 mg twice daily + raltegravir (RAL) 400 mg twice daily + RBT 150 mg/day. All received two nucleoside reverse transcriptase inhibitors and other TB drugs. PK visits occurred on day 12 ± 2. Within-arm HIV-TB outcomes were summarized using proportions and 95% CIs; PK were compared using Wilcoxon tests. Results: Among 71 participants, 52% were women; 72% Black; 46% Hispanic; median age, 37 years; median CD4+ count, 130 cells/mm 3 ; median HIV-1 RNA, 4.6 log10 copies/mL; 46% had confirmed TB. LPV concentrations were similar across arms. Pooled LPV AUC12 (157 203 hours × ng/mL) and Ctrough (9876 ng/mL) were similar to historical controls; RBT AUC24 (7374 hours × ng/mL) and Ctrough (208 ng/mL) were higher, although 3 participants in arm C had RBT Cmax <250 ng/mL. Proportions with week 48 HIV-1 RNA <400 copies/mL were 58%, 67%, and 61%, respectively, in arms A, B, and C. Conclusions: Double-dose LPV/r+RIF and LPV/r+RBT 150mg/day had acceptable safety, PK and TB outcomes; HIV suppression was suboptimal but unrelated to PK. Faster RBT clearance and low Cmax in 3 participants on RBT+RAL requires further study. Abstract : Double-dose lopinavir/ritonavir plus rifampin and standard-dose lopinavir/ritonavir plus 150mg rifabutin were associated with acceptable tuberculosis outcomes, safety, tolerability, and pharmacokinetic profiles in persons with both human immunodeficiency virus and tuberculosis.